Utility of serum nuclear factor erythroid 2-related factor 2 as a potential prognostic biomarker of severe traumatic brain injury in adults: A prospective cohort study - Yan, Xin-Jiang; Zhan, Cheng-Peng; Lv, Yao; Mao, Dan-Dan; Zhou, Ri-Cheng; Xv, Yong-Min; Yu, Guo-Feng (Frontiers in Neurology, 2022)
Objective: Nuclear factor erythroid 2–related factor 2 (Nrf2) may harbor endogenous neuroprotective role. We strived to ascertain the prognostic significance of serum Nrf2 in severe traumatic brain injury (sTBI). Methods: This prospective cohort study included 105 controls and 105 sTBI patients, whose serum Nrf2 levels were quantified. Its relations to traumatic severity and 180-day overall survival, mortality and poor prognosis (Extended Glasgow outcome scale score 1-4) were discerned using multivariate analysis. Results: There was a substantial enhancement of serum Nrf1 levels of patients (median, 10.9 ng/ml versus 3.3 ng/ml; P<0.001), as compared with controls. Serum Nrf2 levels were independently correlative to Rotterdam computed tomography (CT) scores (ρ=0.549, P<0.001; t=2.671, P=0.009) and Glasgow comas scale (GCS) scores (ρ=-0.625, P<0.001; t=-3.821, P<0.001). Serum Nrf2 levels were significantly higher in non-survivors than in survivors (median, 12.9 ng/ml versus 10.3 ng/ml; P<0.001) and in poor prognosis patients than in good prognosis patients (median, 12.5 ng/ml versus 9.4 ng/ml; P<0.001). Patients with serum Nrf2 levels > median value (10.9 ng/ml) had markedly shorter 180-day overall survival time than the other remainders (mean, 129.3 days versus 161.3 days; P=0.002). Serum Nrf2 levels were independently predictive of 180-day mortality (odds ratio, 1.361; P=0.024), overall survival (hazard ratio, 1.214; P=0.013) and poor prognosis (odds ratio, 1.329; P=0.023). Serum Nrf2 levels distinguished the risks of 180-day mortality and poor prognosis with areas under receiver operating characteristic curve (AUCs) at 0.768 and 0.793 respectively. Serum Nrf2 levels > 10.3 ng/ml and 10.8 ng/ml discriminated patients at risk of 180-day mortality and poor prognosis with maximum Youden indices of 0.404 and 0.455 respectively. Serum Nrf2 levels combined with GCS scores and Rotterdam CT scores for death prediction (AUC, 0.897; 95% CI, 0.837-0.957) had significantly higher AUC than GCS scores (P=0.028), Rotterdam CT scores (P=0.007) or serum Nrf2 levels (P=0.006) alone, and for poor outcome prediction (AUC, 0.889; 95% CI, 0.831-0.948) displayed significantly higher AUC than GCS scores (P=0.035), Rotterdam CT scores (P=0.006) or serum Nrf2 levels (P=0.008) alone. Conclusions: Increased serum Nrf2 levels are tightly associated with traumatic severity and prognosis, supporting the considerable prognostic role of serum Nrf2 in sTBI.